2004
DOI: 10.1159/000080698
|View full text |Cite
|
Sign up to set email alerts
|

Volume Flow Rate Evaluation in Patients with Obstructive Arteriosclerotic Disease

Abstract: This study was performed to quantify the volumetric impact of extracranial arteriosclerotic lesions. We investigated patients with different degrees of carotid stenosis as defined by conventional velocity-based duplex criteria and different patterns of collateralization. We studied the volume flow rate (color duplex M-mode device) in 37 patients with symmetrical internal carotid artery (ICA) plaques (<50% stenosis) and compared these data to 43 patients with a unilateral 50–74% stenosis, 75–99% stenosis (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Contralateral carotid occlusion 25 and stenosis Ն50% 23 have been associated with increased carotid volume flow, 24 resulting in an overestimation of the severity of ipsilateral disease; however, we excluded all patients with known contralateral stenoses Ն50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral carotid occlusion 25 and stenosis Ն50% 23 have been associated with increased carotid volume flow, 24 resulting in an overestimation of the severity of ipsilateral disease; however, we excluded all patients with known contralateral stenoses Ն50%.…”
Section: Discussionmentioning
confidence: 99%
“…The study excluded 39 patients who had contralateral carotid stenosis Ն50%, [23][24][25] leaving 216 patients with unilateral carotid stenosis. Completion CA or postprocedural DUS were not available or evaluable for 27 procedures, thereby providing 189 pairs of CA-DUS measurements for analysis.…”
Section: Patientsmentioning
confidence: 99%
“…Meyd et al [24] found that patients with high-grade stenosis had contralateral elevated flow compared with that of patients without high-grade stenosis and age-specific normal subjects (82.6% sensitivity). In the study performed by Doberenz et al [25], the impact of different degrees of extracranial carotid stenosis on the bilateral volume flow in the carotid arteries was evaluated. Patients with a high-grade stenosis (75–99%) or occlusion had a significantly reduced flow as compared with patients with stenosis <75%, but ipsilateral volume flow in patients with stenosis 50–74% only showed a slight, nonsignificant decline compared with that of patients with stenosis <50%.…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-known variability of volume flow estimation using conventional Doppler US,4, 15 time-domain correlation combined with a color M-mode technique5-8 as well as a new dual-beam, angle-independent Doppler device9-12 have been suggested as alternatives. While both methods (somewhat unrealistically) assume a circular symmetric velocity distribution, initial patient studies (involving 10 – 71 subjects) have been encouraging and have demonstrated the complex hemodynamic effects of carotid disease 7-8, 11-12.…”
Section: Discussionmentioning
confidence: 99%
“…While both methods (somewhat unrealistically) assume a circular symmetric velocity distribution, initial patient studies (involving 10 – 71 subjects) have been encouraging and have demonstrated the complex hemodynamic effects of carotid disease 7-8, 11-12. Studies of healthy volunteers to determine normal values on volume flow in the CCA and ICA have involved more subjects (205 and 77, respectively) and have shown an age-related decrease in flow.…”
Section: Discussionmentioning
confidence: 99%